Inclined magnetic fields heat transfer and thermal radiation on fractionalized EMHD Burgers’ fluid flow via bifurcated artery for tumor treatments - Isah Abdullahi; D.G. Yakubu; M.Y. Adamu; Musa Ali; A.M. Kwami (Partial Differential Equations in Applied Mathematics)
In this study, we analyze the electro-magnetohydrodynamic (EMHD) blood flow through a bifurcated artery to enhance tumor treatments. We use the Atangana-Baleanu fractional derivative to model the EMHD blood flow of Burgers' fluid to obtain (derive) the non-dimensionalized form of the equations. Employing suitable variables, we transformed these modeled equations into ordinary differential equations. Analytical solutions of the transformed equations were computed using a combined Laplace transform and the classical method of undetermined coefficients. The results were simulated and presented graphically. The graphical results show that an increase in the Burgers’ parameter leads to a significant reduction in blood flow velocity from the central region of the artery towards the arterial wall, indicating the influence of viscoelastic properties on flow dynamics. Variations in the Eckert number and Joule heating parameters significantly affect blood flow temperature in the bifurcated artery, providing insights into enhancing advective heat transfer for effective tumor treatments and controlled heat management strategies. The findings revealed that increasing fractional parameter values result in a more gradual increase in concentration from the center towards the arterial wall. By exploring the intricate interplay of magnetic fields, heat radiation, Burgers' parameter, and fluid dynamics, this study contributes to advancements in biomedical engineering and medicine.